Disassembling connections: A comparative analysis of the politics of slum upgrading in eThekwini and São Paulo. (June 2022) - Saraiva, Camila
This paper presents an innovative comparison that works creatively with the entangled spatialities of policy mobilities, drawing on a city-to-city cooperation between São Paulo (Brazil) and eThekwini (South Africa) municipalities for the exchange of slum upgrading expertise. The proposed comparative tactic entails tracing the establishment of this connection in order to disassemble the constituent flows and localities merged within it. Subsequently, by posing questions to one another, a relational comparison of the trajectory of slum upgrading policy in each locality is composed, unearthing the political and institutional conditions that preceded the existence of the connection per se. In that sense, both eThekwini and São Paulo are considered equivalent starting points from which local actors engaged in circulating ideas and mobilised slum upgrading policies. This paper not only brings a fresh approach to comparative methods – incorporating political contexts and their extensive overlapping networks of relations alongside a focus on particular policy trajectories – but also contributes to furthering global urban studies in two other ways. First, it provides insight into the processes by which policies are put on the move and localised (or not). Second, it demonstrates how repeated instances of urban practice may be unravelled by allowing each context of policy formation, with its distinctive trajectory of slum upgrading, to speak to one another. In this regard, the comparative analysis identified how, in both São Paulo and eThekwini, the consolidation of democracy was followed by the development of more technocratic approaches to the detriment of earlier slum upgrading initiatives focussed on community empowerment.